Inovação colaborativa na gestão das águas: considerações a partir do protocolo OGA Brasil - Cristina Camila Teles Saldanha (2024)
This thesis is centered on the study of Collaborative Innovation, which corresponds to new solutions designed through collaboration to solve complex problems, as happens in Water Resources Management in which interested actors mobilize in favor of alternatives to issues linked to water availability. To assist in water management, the Water Governance Observatory network devised a Protocol that aims to diagnose the River Basin Committees, a management unit at the local level, considering the river basins, whose participatory configuration makes it possible to provide suitable spaces for collaboration and develop innovations. In this context, the objective of this research is to analyze to what extent the representatives of the River Basin Committees consider that the initiatives resulting from the Water Governance Monitoring Protocol contribute to collaborative innovation in Water Resources Management. Specifically, this study also aims to: i) identify how the actors involved understand “innovation” in Water Resources Management; ii) show the initial conditions of innovation following the adoption of the Protocol in the committees; and iii) identify and explain categories whose presence or absence may represent barriers or facilitators in collaborative innovation processes – opening the design of the governance, learning and leadership arrangement. For this investigation, an Analysis Scheme was composed using the theoretical apparatuses of governance and collaborative innovation that follows the logic of antecedents, innovation process with the analysis categories selected a priori and results. This is an empirical theoretical work of a qualitative, descriptive and exploratory nature in which case studies of the river basin committees of the Doce River and Mucuri River were analyzed. Data collection took place in 2023 with the techniques of: documentary survey to characterize the selected cases, semi-structured interviews carried out with eleven research subjects among the members of the network and representatives of the committees studied and non-participant observation at an event promoted by the Observatory. From the triangulation of the interviewees' perceptions, it is concluded that the network and its tool require greater maturity to be a means of innovating in committees, just as it is necessary to reduce the barriers of ready decisions, apparent deliberation, hidden conflicts, consensus presumption and lack of mutual understanding between the actors; and enhance learning facilitators caused by critical reflections and the emergence of local leaders to promote collaborative innovation in water management.